How human is human? : - Ishiguro, Hiroshi (Japan Publishing Industry Foundation for Culture (JPIC), 2020)
How Human Is Human?: The View from Robotics Research presents an overview of various androids created by its author, Hiroshi Ishiguro, along with episodes and difficulties encountered during their development. Unlike the industrial robots so commonly seen in today’s factories, Dr. Ishiguro’s androids are designed with a focus on providing new tools for human interaction and communication. Of particular note are his Geminoid series androids, which are designed to exactly duplicate the appearance of actual living beings (in the case of the latter, Ishiguro himself), providing insights into psychological phenomena arising from the experience of encountering one’s doppelganger. These androids further allow for remote operations over the Internet, allowing users to project their voice and even movements, thereby establishing a sense of presence that is impossible through commonplace technologies such as video conferencing. These androids thus represent a first step toward telepresence technologies only encountered today in works of science fiction.